Portuguese public discussion weighting report: possible participatory instrument in Brazil - Britto, Marcel [UNESP]; Oliveira, Celso Maran de (Univ Caxias Sul, Centro Ciencias Comunicacao, 2022)
The Portuguese legislation, recognizing the centrality of decision -making weighting and the need to guarantee popular participation in the urban sphere, obliges the public power to provide feedback to the manifestations received during the period of public discussion - this is the weighting report - so the authority is bound to respond, reasonably, in writing, to complaints, observations, suggestions and requests for clarification from interested parties. Thus, understanding the public discussion weighting report proves to be important for the improvement of participatory democracy, that, for both Environmental and Urban Law, should be the way of constructing public policies in Brazil, giving rise to its study based on descriptive and qualitative research from bibliographic and documentary sources whose purpose is to present and explain highlighted aspects of the instrument, since its inception. general concept to its structure and dynamics in Portuguese law. With the study in a comparative perspective the work: presents the definitions, principiological roots, and the detailed forecast of the public discussion weighting report in Portuguese Law; continues to address aspects of its effectiveness; analyzes the conceptual, practical and operational bases of the public discussion weighting report for its importation from the Portuguese order to the Brazilian; proposes the structuring model of the weighting report until concluding by the usefulness and necessity of the weighting report of public discussion as a tool for improving participatory democracy in Brazil, environmental and urban issues.
Keywords: Public discussion weighting report; Participatory democracy.